Hubungan Pengetahuan Tentang Kehamilan Remaja Dengan Sikap Dalam Pencegahan Kehamilan Pada Siswi Di SMK Negeri 6 Bengkulu Utara Tahun 2025 - Hasanah, Jumrotul; Yulianti, Syami; Sulastri, Mepi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
According to data from the World Health Organization (WHO), an estimated 12.7 million births will occur in adolescent girls aged 15-19 years in 2023, with approximately 500,000 cases occurring in girls aged 10-14 years. This figure represents 10% of the total global births. Therefore, by 2023, the global adolescent birth rate will reach 41.3 births per 1,000 girls aged 15-19 years (WHO, 2023). The purpose of this study was to determine the relationship between knowledge about adolescent pregnancy and attitudes toward pregnancy prevention among female students at State Vocational High School 6, North Bengkulu, in 2025. The research method used was a cross-sectional approach. The sample in this study consisted of 30 female students selected using a total sampling technique. Data were collected using a questionnaire adapted from Igusti's (2021) research, which has been tested for validity and reliability. Data analysis was performed using the Chi-Square Test. The results showed that the majority of respondents (56.7%) had sufficient knowledge. A total of 80.0% of respondents had positive attitudes toward pregnancy prevention. Statistical tests showed a significant relationship between knowledge about teenage pregnancy and attitudes toward pregnancy prevention, with a p-value of 0.002. It is hoped that the results of this study will contribute to schools strengthening reproductive health education programs to prevent teenage pregnancy.